2011
DOI: 10.1186/1744-8069-7-46
|View full text |Cite
|
Sign up to set email alerts
|

Intracisternal Administration of NR2 Subunit Antagonists Attenuates the Nociceptive Behavior and p-p38 MAPK Expression Produced by Compression of the Trigeminal Nerve Root

Abstract: BackgroundWe investigated the role of the central NMDA receptor NR2 subunits in the modulation of nociceptive behavior and p-p38 MAPK expression in a rat model with compression of the trigeminal nerve root. To address this possibility, changes in air-puff thresholds and pin-prick scores were determined following an intracisternal administration of NR2 subunit antagonists. We also examined effects of NR2 subunit antagonists on the p-p38 MAPK expression.ResultsExperiments were carried out using male Sprague-Dawl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 51 publications
(78 reference statements)
0
22
0
Order By: Relevance
“…In the present study, the injection of NMDA or mGlu1 receptor antagonists into the DRt reduced formalin‐induced secondary allodynia and hyperalgesia. This evidence, along with other studies, supports the role of glutamate receptors in supraspinal modulation of inflammatory or neuropathic pain (Coutinho et al ., ; Urban & Gebhart, ; Varty et al ., ; Ansah et al ., ; Jeon et al ., ). Other studies have shown the importance of spinal mechanisms (Nozaki‐Taguchi & Yaksh, ; Pogatzki et al ., ) and the contribution of other supraspinal structures (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, the injection of NMDA or mGlu1 receptor antagonists into the DRt reduced formalin‐induced secondary allodynia and hyperalgesia. This evidence, along with other studies, supports the role of glutamate receptors in supraspinal modulation of inflammatory or neuropathic pain (Coutinho et al ., ; Urban & Gebhart, ; Varty et al ., ; Ansah et al ., ; Jeon et al ., ). Other studies have shown the importance of spinal mechanisms (Nozaki‐Taguchi & Yaksh, ; Pogatzki et al ., ) and the contribution of other supraspinal structures (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…NMDA receptors are formed by several subunits, with the NMDA-NR2B subunits reported to contribute to the development of central sensitization and neuropathic pain 58 . Specifically, it has been reported that NR2B phosphorylation of dorsal horn neurons is enhanced in neuropathic 59 and post-inflammatory 60 pain models, and the use of NR2B antagonists has been shown to reduce inflammatory 61 , 62 , peripheral 61 , 63 and spinal cord injury-induced neuropathic pain 64 . Furthermore, σ 1 R activation has been associated with NMDA-NR2 phosphorylation in the hippocampus 65 and this phenomenon was reduced in σ 1 R KO mice 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The air-puff threshold was determined as the air-puff pressure at which each rat responded in 50% of the trials. The cut-off pressure for the air puff was 40 psi, as described previously [ 21 22 23 24 ]. The naïve rats did not respond to a pressure of less than 40 psi.…”
Section: Methodsmentioning
confidence: 99%